AN EVALUATION OF THE OCCUPATIONAL EXTERNAL RADIATION EXPOSURE OF PERSONNEL IN NUCLEAR MEDICINE PRACTICES (2010–2020). Issue 5 (4th April 2022) - Sahmaran, T; Atılgan, H I; Nur, S; Sahutoğlu, G; Yalcın, H
Abstract: The aim of this study was to examine the radiation doses received by personnel working in the Nuclear Medicine Department between 2010 and 2020. The data obtained were compared with the dosages recommended by international authorities. The UNSCEAR 2008 report stated that the worldwide annual average effective dose to which personnel were exposed when monitored between 2000 and 2002 was 0.70 and 1.40 mSv, respectively. In this report, 0.7 mSv refers to the dose of all monitored personnel, and 1.4 mSv refers to the dose above the detection limit. In this study, the annual average effective dose value for personnel exposed to radiation was calculated as 1.65 mSv. This value represents the dose above the detection limit. Although the individual dose results are below the recommended annual dose limit, it should not be forgotten that more effort should be made to reduce radiation doses using the as low as reasonable achievable principles.